Inca Garcilaso: founder of discursivity, founder of discontinuity - Ruiz, Facundo (Anales de Literatura Hispanoamericana, 2021)
Inca Garcilaso de la Vega and, especially, his Comentarios reales are to literature what Bach and his The Musical Offering are to music: in the conflict of interpretation, the founding of the struggle for meaning as an existence regime. To achieve this, the Inca brings together language’s both original suspicions in his Comentarios: that language doesn’t say exactly what it says; and that there are many things that speak without being language. And thus, he redefines the way meaning is produced, and changes, irreversibly, the space of distribution where signs can be signs, opening a different (but not separate) territory of intelligibility that repairs, even today, the cultural map of an unexpected but definitive ecumene. The language with which he does it, the name and figure of the author to whom he attributes it, and the temporality that he builds in order to place his work, are the three concerns –and principles– that guide this essay.